Improving Learning of Addition Count Operation through Realistic Mathematics Education Approach for Mildly Retarded Children: Classroom Action Research VII SLB Autisma Mutiara Bangsa Pratama Padang - Desma Dahliawaty; Zulmiyetri Zulmiyetri; Irdamurni Irdamurni; Iga Setia Utami (Universitas Muhammadiyah Enrekang, 2023)
The purpose of this study was to improve student learning outcomes by applying Realistic Mathematics Education (RME) in addition material in class VII SLB Autisma Mutiara Pratama. The research method used was classroom action research together with the class teacher at Mutiara Mutiara Autism SLB and two students in this study including mildly retarded. Researchers used data collection techniques through observation, testing, and documentation. The evaluation tools used mean observation and learning outcomes tests and data analysis techniques with quantitative descriptions and qualitative data analysis. The results of the study are described by each cycle. Each cycle is divided into four stages, namely planning, implementation, observation and reflection. According to the results of this study, the use of the mathematics education approach (RME) VII grade students can also improve student learning outcomes through media and linking to everyday life The average percentage of observation results of student activity cycle I = 68%, Cycle II = 82% while the average percentage of pre-cycle student learning outcomes = 30%, cycle I = 45%, cycle II = 75%.